The storyteller's secret : from TED speakers to business legends, why some ideas catch on and others don't - Gallo, Carmine (New York : St. Martin's Press, 2016)
Internationally bestselling author Carmine Gallo reveals the secrets to telling powerful, inspiring, and game-changing stories that will help you achieve any goal. --Publisher
Preface: Your story is my passion ; Introduction: Richard Branson, dopamine, and the Kalahari Bushmen -- Part I: Storytellers who ignite our inner fire. What makes your heart sing? ; From T-shirt salesman to mega producer ; Conquering stage fright to sell out Yankee Stadium ; A rock star rediscovers his gift in the backstory of his youth ; Change your story, change your life ; The power in your personal legend ; A coffee king pours his heart into his business ; We're not retailers with a mission, we're missionaries who retail ; If you can't tell it, you can't sell it -- Part II: Storytellers who educate. How a spellbinding storyteller received TED's longest standing ovation ; Turning sewage into drinking water ; What you don't understand can (and does) hurt you ; The $98 pants that launched an empire ; Japan unleashes its best storytellers to win Olympic gold ; A funny look at the most popular TED talk of all time ; Dirt, cigars, and sweaty socks put a marketer on the map ; A burger with a side of story -- Part III: Storytellers who simplify. If something can't be explained on the back of an envelope, it's rubbish ; The Evangelizer in Chief ; A film mogul's granddaughter cooks up her own recipe for success ; The storytelling astronaut wows a TED audience ; "Dude's selling a battery" and still inspires ; An entrepreneur makes Shark Tank history -- Part IV: Storytellers who motivate. Find your fight ; The hospital Steve Jobs would have built ; A hotel mogul turns 12,000 employees into customer service heroes ; A revolutionary idea that took off on the back of a napkin ; When Amy lost her legs, she found her voice ; From Hooters to the C-suite -- a former waitress shares her recipe for success ; Trading Wall Street riches for the promise of a pencil ; The ice bucket challenge melts the hearts of millions ; His finest hour -- 180 words that saved the world -- Part V: Storytellers who launch movements. Great storytellers are made, not born ; Millions of women "lean in" after one woman dares to speak out ; The 60-second story that turned the wine world on its side ; From my heart rather than from a sheet of paper ; Story, story, story -- Conclusion: The storyteller's universe ; The storyteller's toolkit ; The storyteller's secrets at a glance ; The storyteller's checklist.
Includes bibliographical references (pages 245-260) and index.
Keywords: Business communication; Communication in management; Communication in organizations; Storytelling; Inspiration; Persuasion (Psychology)